Decoding the Buyer’s Mind: The Role of Promotion and Brand Image in Purchase Decisions - Mareta, Futri Zamnis; Razak, Ismail; Yuaniko, Yuaniko (Marketing and Business Strategy, 2025)
This study aims to analyze the extent to which promotion and brand image influence the purchasing decisions of Shopee customers in East Jakarta. Using a quantitative approach with survey methods and multiple linear regression analysis, the results of the study indicate that both promotion and brand image simultaneously and partially have a positive and significant effect on purchasing decisions. This finding means that attractive promotions such as discounts, cashback, and flash sales, as well as a strong and positive brand image can encourage consumers to make purchases. This study investigates how promotion and brand image influence purchasing decisions among Shopee customers in East Jakarta using a quantitative survey and regression analysis. Results show that brand image has a significant positive effect, while promotion does not significantly influence purchasing decisions when examined individually. The managerial implications of these findings are that Shopee management needs to continue to optimize promotional strategies creatively and consistently to maintain and increase customer loyalty. In addition, building and maintaining a positive brand image through service quality, platform appearance, and good interaction with consumers are important keys to strengthening competitiveness in the competitive e-commerce market.